Multiple Sclerosis in the Mount Etna region: possible role of volcanogenic trace elements. - Alessandra Nicoletti (Public Library of Science (PLoS), 2013)
Background Trace elements have been hypothesised to be involved in the pathogenesis of Multiple Sclerosis and volcanic degassing is the major natural sources of trace elements. Both incidence of Multiple Sclerosis in Catania and volcanic activity of Mount Etna have been significantly increased during the last 30 years. Due to prevailing trade winds direction, volcanic gases from Etna summit craters are mostly blown towards the eastern and southern sectors of the volcano. Objective To evaluate the possible association between Multiple Sclerosis and exposure to volcanogenic trace elements. Methods We evaluated prevalence and incidence of Multiple Sclerosis in four communities (47,234 inhabitants) located in the eastern flank and in two communities (52,210 inhabitants) located in the western flank of Mount Etna, respectively the most and least exposed area to crater gas emissions. Results A higher prevalence was found in the population of the eastern flank compared to the population of the western one (137.6/100,000 versus 94.3/100,000; p-value 0.04). We found a borderline significantly higher incidence risk during the incidence study period (1980-2009) in the population of the eastern flank 4.6/100,000 (95% CI 3.1-5.9), compared with the western population 3.2/100,000 (95% CI 2.4-4.2) with a RR of 1.41 (95% CI 0.97-2.05; p-value 0.06). Incidence risks have increased over the time in both populations reaching a peak of 6.4/100,000 in the eastern flank and of 4.4/100.000 in the western flank during 2000-2009. Conclusion We found a higher prevalence and incidence of Multiple Sclerosis among populations living in the eastern flank of Mount Etna. According to our data a possible role of TE cannot be ruled out as possible co-factor in the MS pathogenesis. However larger epidemiological study are needed to confirm this hypothesis.